Pemikiran Hukum Islam Mazhab Syiah dan Ahmadiyah - Ikram, Muhammad Furqanul; Taher, Muhammad Rafli HI; F, Fatmawati; Sultan, Lomba (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
After occurred taá¸¥kÄ«m between caliph Ali and Muawiyah which ended in deceit which caused caliph Ali to be removed from the reins of government power. The taá¸¥kÄ«m process then gave birth to three groups of Muslims, two in the form of a majority group and one in the form of a minority group. The groups that the author refers to are groups that were pro Mu'awiyah, groups that were pro 'Ali which were later named Shiites and minority groups that used to support 'Ali then defected and renamed themselves khawÄrij. In other parts of the world, groups have emerged calling themselves reformers (mujaddid) in Islam. This organization is called Ahmadiyah, founded by Hazrat Mirza Ghulam Ahmad Alqadiani, a Mujaddid of the 14th century Hijriyah who had the titles of Almasih and Mahdi, based on inspiration from Allah SWT. which he received on December 1, 1888.